2016
DOI: 10.1371/journal.pone.0146848
|View full text |Cite
|
Sign up to set email alerts
|

Toward FRP-Based Brain-Machine Interfaces—Single-Trial Classification of Fixation-Related Potentials

Abstract: The co-registration of eye tracking and electroencephalography provides a holistic measure of ongoing cognitive processes. Recently, fixation-related potentials have been introduced to quantify the neural activity in such bi-modal recordings. Fixation-related potentials are time-locked to fixation onsets, just like event-related potentials are locked to stimulus onsets. Compared to existing electroencephalography-based brain-machine interfaces that depend on visual stimuli, fixation-related potentials have the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…Such contamination cause problems either when the EOG artifacts appear in the time intervals that are the main focus of analysis or when they are present during intervals used for baseline correction (Finke et al, 2016; Nikolaev et al, 2016). In addition, EEG components within the first 200 ms after fixation onset depend on the size of saccade preceding the fixation (Nikolaev et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such contamination cause problems either when the EOG artifacts appear in the time intervals that are the main focus of analysis or when they are present during intervals used for baseline correction (Finke et al, 2016; Nikolaev et al, 2016). In addition, EEG components within the first 200 ms after fixation onset depend on the size of saccade preceding the fixation (Nikolaev et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The gaze fixation and FRP data complement each other when used as an input to a hybrid interface: the fixation onset provides the temporal marker required for EEG segmentation and FRP extraction, the FRP provides features for a passive BCI classifier that automatically recognizes target finding (in the case of visual search) or issuing a command (in intentional dwell-based control), and the gaze position indicates the target (Protzak et al, 2013; Finke et al, 2016). This combination may enable fluent interaction both in visual search (Finke et al, 2016; see also Introduction) and in intentional dwell-based control (Protzak et al, 2013, and the current study).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it can be expected that several words or pictograms are shown in parallel in a more realistic setting. The combination of EEG with an eye tracker would allow to relate the neural activity to each pictogram or word [1520]. Eye movements towards the items could be used as time points of reference for the EEG segmentation in epochs, instead of the onset of stimuli popping up on the screen.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was suggested that BCI technology could be transferred to relevance detection in human-computer interaction (HCI), because EEG combined with an eye tracker can be used to predict which of several items displayed at the same time on the screen are task-relevant for the user [1520]. The application of BCI technology to HCI is presumably most useful and convenient for the user if the information (e.g.…”
Section: Introductionmentioning
confidence: 99%